Pacific Islands Families Study: psychological distress among mothers of Pacific children living in New Zealand - Janis Paterson; El‐Shadan Tautolo; Leon Iusitini; Steve Taylor (Elsevier, 2016)
Abstract Objective: This study investigated: 1) the prevalence of psychological distress among a cohort of mothers of Pacific children; and 2) the socio‐demographic and lifestyle variables associated with psychological distress. Method: The Pacific Islands Families (PIF) Study is a longitudinal investigation of a cohort of Pacific children born in Auckland, New Zealand, and their mothers and fathers. The 12‐item General Health Questionnaire (GHQ12) was used to assess psychological distress among mothers (N=851) at about 11 years postpartum. Results: Current psychological distress was reported by 19% of mothers, and six explanatory variables were significantly associated with maternal psychological distress: stressful life events, postnatal depression, marital status, maternal education, ethnicity and cultural alignment. Conclusion: These findings suggest that the mental health of Pacific people varies by particular ethnic group and cultural alignment. This highlights the need for culturally appropriate evaluation and treatment for at‐risk Pacific mothers that will break down psychological, cultural and economic barriers to accessing help for psychological distress. Implications: By learning about factors that are potentially modifiable we can begin to identify the most appropriate ways to address their impact on psychological distress among Pacific women.